1998
DOI: 10.2307/3761280
|View full text |Cite
|
Sign up to set email alerts
|

Ascomycetes from Freshwater Habitats: Ascolacicola aquatica Gen. et sp. nov. and a New Species of Ascotaiwania from Wood Submerged in a Reservoir in Hong Kong

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Asexual morphs associated with the Savoryellales were described for Canalisporium grenadoideum (as Ascothailandia grenadoidea sexual morph, Sri-indrasutdhi et al 2010 ) and three species of Ascotaiwania were linked with Brachysporiella -like dematiaceous hyphomycetes, A. mitriformis and A. sawadae (as Monotosporella , Ranghoo & Hyde 1998 , Sivichai et al 1998 ) and A. limnetica (this study). With some reservations Acarocybiopsis was suggested as another suitable genus for asexual morphs of Ascotaiwania ( Réblová & Seifert 2004 ).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Asexual morphs associated with the Savoryellales were described for Canalisporium grenadoideum (as Ascothailandia grenadoidea sexual morph, Sri-indrasutdhi et al 2010 ) and three species of Ascotaiwania were linked with Brachysporiella -like dematiaceous hyphomycetes, A. mitriformis and A. sawadae (as Monotosporella , Ranghoo & Hyde 1998 , Sivichai et al 1998 ) and A. limnetica (this study). With some reservations Acarocybiopsis was suggested as another suitable genus for asexual morphs of Ascotaiwania ( Réblová & Seifert 2004 ).…”
Section: Discussionmentioning
confidence: 58%
“…All known life-histories discussed here were established experimentally, i.e. Ascotaiwania ( Ranghoo & Hyde 1998 , Sivichai et al 1998 , this study), Canalisporium ( Sri-indrasutdhi et al 2010 ), Conioscypha ( Réblová & Seifert 2004 , Zelski et al 2014 ), Helicoön farinosum ( Fallah et al 1999 ), Pleurothecium ( Fernández et al 1999 ), Pleurotheciella ( Réblová et al 2012 ), Sterigmatobotrys ( Réblová & Seifert 2011 ) and the new genera described in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The protologue described only one asexual morph ( Maggi et al 1978 ), but three were reported later by Constantinescu & Samson (1982) and Tzean & Chen (1989) . No sexual morph has been linked to this species, but another Triadelphia species, T. uniseptata , was reported as the asexual morph of Ascolacicola aquatica , a member of Sordariales ( Ranghoo & Hyde 1998 , Ranghoo et al 1999 ). BLAST homology searches with the LSU sequences of the ex-type isolates of T. heterospora (generic type), T. pulvinata and T. disseminata did not confirm an affinity of the genus with the Sordariales and the closest matches were members of Hypocreomycetidae in the orders Microascales (such as Dendroclathra lignicola EU873530 and Graphium fabiforme KM495387) and Hypocreales (such as Hypomyces subiculosus AJ459309 and Elaphocordyceps inegoensis AB027368) with 91–94 % identity.…”
mentioning
confidence: 99%